Pengaruh Strategi Pemasaran Dan Kepuasan Pelanggan terhadap Volume Penjualan Bouqet Bunga Melalui Kualitas Pelayanan Di Kecamatan Medan Tembung - Siti Ariska; Yulia Tiara Tanjung; Uswatun Hasanah (Departement of Mathematics Education, 2023)
This research aims to determine the extent of the influence of marketing strategy and customer satisfaction on the sales volume of flower bouquets through service quality in Medan Tembung sub-district. The population in this study was the Hai Gallery Medan store customers, totaling 250 customers. The sampling technique uses the Slovin formula with an error tolerance of 5% and uses the Sample Random Sampling technique so that the total sample is 154 respondents. The analysis used is multiple linear regression. The results of this thesis show the influence of marketing strategy on sales volume with the result tcount 3.007 > ttable 0.1322 and significant 0.003 < 0.05, so marketing strategy has a partially significant effect on sales volume. The effect of customer satisfaction on sales volume with the results of tcount 8.645 > ttable 0.1322 and significant 0.000 <0.05, then customer satisfaction has a partially significant effect on sales volume. The influence of marketing strategy on service quality with the results of tcount 3.643 > ttable 0.1322 and significant 0.000 <0.05, then marketing strategy has a significant effect partially on service quality. The effect of customer satisfaction on service quality with the results of tcount 3.998 > ttable 0.1322 and significant 0.025 <0.05, then customer satisfaction has a partially significant effect on service quality. The effect of service quality on sales volume with the results of tcount 2.542 > ttable 0.1322 and significant 0.002 <0.05, then service quality has a partially significant effect on sales volume. The direct effect of marketing strategy on sales volume is 0.123, while the indirect effect is 0.053, so it can be concluded that the intervening variable, namely the service quality variable, is not able to mediate marketing strategy on sales volume. The direct effect of customer satisfaction on sales volume is 0.564, while the indirect effect is 0.020, so it can be concluded that the intervening variable, namely the service quality variable, is not able to mediate customer satisfaction on sales volume.